Bioleptin as a useful marker of metabolic status in children with diabetes mellitus type 1 - Jakubek-Kipa, Katarzyna; Galiniak, Sabina; Łagowska, Katarzyna; Krupa, Izabela; Ludwin, Aleksandra; Tabarkiewicz, Jacek; Mazur, Artur (Frontiers in Endocrinology, 2023)
The purpose of our study was to measure the level of leptin and biologically active leptin (bioLEP) in children with type 1 diabetes, depending on the duration of diabetes and its degree of metabolic control. The study included 94 children (58 boys and 36 girls). In a group of children with diabetes, 40 patients were newly diagnosed with type 1 diabetes, 40 children who have diabetes for more than a year (20 with good metabolic control and 20 with poor metabolic control). The control group consisted of 14 healthy children. The serum level of leptin and bioLEP was measured using a sandwich enzyme-linked immunosorbent assay. To our knowledge, this is the first study to describe bioLEP levels among diabetic children with different forms of disease control. Lower levels of leptin were found in children with diabetes compared to healthy children. Furthermore, we found a statistically higher concentration of leptin in the group of children with newly diagnosed diabetes compared to children from the diabetic group with poor metabolic control and lower than healthy children (11.19 vs. 7.84 and 20.94 ng/mL). Moreover, children in the metabolically well-controlled group had statistically lower levels of this hormone (5.11 ng/mL) than healthy children. Leptin concentrations differed significantly between underweight, overweight, and obese children. In our study, the level of bioLEP differed significantly between children in the newly diagnosed diabetes group and children in the long-term, poorly controlled diabetes group and healthy controls. Despite many studies published in recent years, many aspects of leptin secretion, action, and mechanisms of its influence on carbohydrate and fat metabolism are still to be clarified. In our opinion, studies evaluating the status of bioLEP in diabetes can also contribute to a better understanding of the mechanisms regulating metabolism.